Factors affecting student satisfaction in e-learning. (7th June 2022) - Chang, Victor; Liu, Meiyi; Xu, Qianwen Ariel; Xiong, Chang
The purpose of this study is to investigate the factors that influence college student satisfaction with e-learning. Authors also attempt to explore the relationship between usage intention and factors affecting e-learner satisfaction. Both qualitative and quantitative methods were adopted for this study. 224 undergraduates from Suzhou participated in the data collection process. Correlation analysis and multiple regression analysis were conducted to examine relationships between various antecedents and the usage intention of online courses. It is found that external factors such as class interaction and the quality of teachers impose a significant impact on student satisfaction. Internal factors such as the level of self-discipline and the degree of concentration also influence satisfaction. Both external factors and internal factors had positive effects on the usage intention of online courses. The findings may assist faculty in designing quality online courses to meet students' needs better and improve student satisfaction.